Pengaruh Lingkungan Kerja, Kepuasan Kerja Dan Organizational Citizenship Behavior Terhadap Kinerja Dosen - Novita Dona Sartika; Hazmanan Khair (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2022)
This study aims to determine the effect of the work environment, job satisfaction and Organizational Citizenship Behavior on the performance of lecturers at the Ganesha Polytechnic Medan both partially and simultaneously. This study uses a quantitative descriptive method using a normative approach (legal research) for secondary data and an empirical approach to obtain primary data through field research. The population in this study were all permanent lecturers at the Ganesha Polytechnic Foundation, Medan, totaling 38 lecturers in sampling using probability sampling techniques. The sampling technique used is the Questionnaire technique using the Likert Summated Rating method. With the help of SPSS 24.00 (Statistical Product and Service Solutions) software. The results showed that simultaneously the work environment, job satisfaction and organizational citizenship behavior had a significant effect on the performance of lecturers at the Ganesha Polytechnic Medan. The results of the study partially the work environment has a significant effect on the performance of lecturers at the Ganesha Polytechnic Medan. Partially, job satisfaction has a significant effect on the performance of lecturers at the Ganesha Polytechnic Medan. Partially, organizational citizenship behavior has a significant effect on the performance of lecturers at the Ganesha Polytechnic Medan.